Supramolecular Organization of Diaryliodonium Dicyanoargentates(I) Provided by Iodine(III)–Cyanide Halogen Bonding; Inorganics; Vol. 13, iss. 5 - Aliyarova I. S. Irina Sergeevna; Koziakova A. V. Anastasiia; Ivanov D. M. Daniil Mikhaylovich; Soldatova N. S. Nataliya Sergeevna; Postnikov P. S. Pavel Sergeevich (2025, 2025)
Title screen